2018
DOI: 10.1111/ner.12740
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic Stimulation Improves Quality of Life of Patients Aged 61 Years or Older With Short Duration of Parkinson’s Disease

Abstract: Patients aged 61 years or older benefited from STN-DBS regardless of short (≤8 years) or longer (>8 years) disease duration. Our results contribute to the debate about DBS selection criteria and timing and call for prospective confirmation in a larger cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
1
22
1
Order By: Relevance
“…As a general trend in the STN‐DBS group, patient selection resulted in the lowest mean age at intervention, shortest disease duration, and least impairment for baseline clinical outcome parameters. Consistent with previous studies that have identified the relative importance of these factors, in this highly selected group, improvements were observed for QoL, motor, nonmotor outcomes. As mentioned previously, our results indicate that the beneficial effects of STN‐DBS may be particularly favorable if a reduction of dopaminergic medication may result in an improvement of specific nonmotor outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As a general trend in the STN‐DBS group, patient selection resulted in the lowest mean age at intervention, shortest disease duration, and least impairment for baseline clinical outcome parameters. Consistent with previous studies that have identified the relative importance of these factors, in this highly selected group, improvements were observed for QoL, motor, nonmotor outcomes. As mentioned previously, our results indicate that the beneficial effects of STN‐DBS may be particularly favorable if a reduction of dopaminergic medication may result in an improvement of specific nonmotor outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical assessments were carried out at preoperative baseline (MedON/MedOFF) and at 6‐month follow‐up after surgery (MedON‐StimON) with the following scales: Motor disorder: UPDRS‐III, UPDRS‐IV, and Hoehn and Yahr scale were used to investigate motor impairment, complications, and global motor dysfunction The therapeutic medical regimen was recorded calculating the levodopa equivalent daily dose (LEDD) according to the method of Tomlinson et al The PD Questionaire‐8 (PDQ‐8) has previously been used in patients with PD and STN‐DBS, APO, and IJLI . The PDQ is recommended for QoL assessments by the Movement Disorders Society Scales Committee and has been commonly used studies on invasive therapies of advanced PD .…”
Section: Methodsmentioning
confidence: 99%
“…More recently, a study by Choi et al found significant sustained improvements in sleep disturbances up to 3 years after STN-DBS [6]. But the study was limited by the single center design of their study, the cohort sample size (45 patients completed the last follow-up, and the mean disease duration of patients (17.2 years ± 6.2), which is longer than most DBS studies [12,18,49,51].…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, from our relatively short follow-up, we cannot predict which factors contribute to long-term QoL improvement, in particular, as in some patients a relatively long time may be required to find stable effective stimulation parameters or to recover from medication withdrawal. A longer follow-up including neuropsychological and non-dopaminergic NMS as well as axial motor symptoms, such as falls, is required to address the long-term QoL outcome [46,47].…”
Section: Accepted Manuscriptmentioning
confidence: 99%